Art Directors Club Milano. : Terzo annual. - Neuburg, Till (Milano : Art Directors Club, 1970)
Contents: Awards ; Special mentions ; Campaign of complete advertising unit employing different media ; Ad or series of ads for consumer goods in magazines ; Ad or series of ads in newspapers ; Ad or series of ads in trade magazines ; Sales poster ; Poster for social or cultural events ; Direct mail ; Editorial design for books ; Editorial design for magazines ; Corporate identity ; Point of sale ; Packaging ; Exhibitions, trade fairs, complete stand fittings ; TV/Cinema
Italiaans & Engels
boek